2008
DOI: 10.1088/1742-6596/98/4/042006
|View full text |Cite
|
Sign up to set email alerts
|

Polarization effects on the dielectric properties of molten AgI

Abstract: The results are reported of molecular dynamics simulations of the static longitudinal dielectric and response functions for molten AgI at 923 K using two ionic models. The first one is a rigid ion model, while in the second the induced dipole moments of the anions are added to the effective pair potentials of the first. It is derived theoretically that the dielectric functions for the polarizable ion model are determined by spatial correlations of charge and dipole moment densities. The charge structure factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(37 reference statements)
2
3
0
Order By: Relevance
“…As it can be seen in the inset of Figure , the RIM S ZZ ( k ) at k < 0.4 Å -1 practically fits the theoretical long-wavelength limit approximation derived for rigid ion models, i.e., S ZZ ( k → 0) = k 2 / k D 2 , where k D = (4π z 2 e 2 ρ N / k B T ) 1/2 is the Debye wave number with z = z + = | z - |. , However, the corresponding values for PIM1 and PIM2s are higher than those for RIM, with those for PIM1 increasing much faster because its S AgAg ( k ) goes to its shoulder at about 1 Å -1 . Recently we derived theoretically that the long-wavelength limit for ionic systems with point dipoles, as PIM1 and PIM2s, is given by S ZZ ( k → 0) = [1 − C ( k )] k 2 / k D 2 , where C ( k ) is related to spatial correlations between charge and dipole moment densities . As can be seen in the inset of Figure , the three models fulfill their theoretical k → 0 limits derived in ref .…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…As it can be seen in the inset of Figure , the RIM S ZZ ( k ) at k < 0.4 Å -1 practically fits the theoretical long-wavelength limit approximation derived for rigid ion models, i.e., S ZZ ( k → 0) = k 2 / k D 2 , where k D = (4π z 2 e 2 ρ N / k B T ) 1/2 is the Debye wave number with z = z + = | z - |. , However, the corresponding values for PIM1 and PIM2s are higher than those for RIM, with those for PIM1 increasing much faster because its S AgAg ( k ) goes to its shoulder at about 1 Å -1 . Recently we derived theoretically that the long-wavelength limit for ionic systems with point dipoles, as PIM1 and PIM2s, is given by S ZZ ( k → 0) = [1 − C ( k )] k 2 / k D 2 , where C ( k ) is related to spatial correlations between charge and dipole moment densities . As can be seen in the inset of Figure , the three models fulfill their theoretical k → 0 limits derived in ref .…”
Section: Resultssupporting
confidence: 66%
“…Recently we derived theoretically that the long-wavelength limit for ionic systems with point dipoles, as PIM1 and PIM2s, is given by S ZZ ( k → 0) = [1 − C ( k )] k 2 / k D 2 , where C ( k ) is related to spatial correlations between charge and dipole moment densities . As can be seen in the inset of Figure , the three models fulfill their theoretical k → 0 limits derived in ref .
7 Charge static structure factors, S ZZ ( k ), from MD simulations of molten AgI at 923 K using the RIM (dotted line), PIM1 (solid line), and PIM2s (dashed line).
…”
Section: Resultssupporting
confidence: 62%
“…12,13 However, the calculated S(k) failed to reproduce the almost featureless broad main peak between the shoulder at 1.8 Å −1 and the maximum at around 2.8 Å −1 , as well as the prepeak that appears at around 1 Å −1 , 14 exhibited by the neutron diffraction (ND) data obtained by Inui et al, 15 Shirakawa et al, 16 and Kawakita et al 17,18 In fact, at first glance the prepeak appears as a shoulder, but there is a small maximum at around 1 Å −1 . More recently, Bitrian et al [19][20][21][22] showed that the inclusion of the anions polarizability in the VR potentials accounts for the experimental prepeak of the S(k) for molten AgI, as well as improves the experimental almost featureless broad main peak. Actually, Bitrian et al use the potential parameter values proposed by Shimojo and Kobayashi, 23 who slightly modified the PRV parameterization in order to reproduce the α-phase features at the appropriate experimental density.…”
Section: Introductionmentioning
confidence: 99%
“…In SM dipole is presented by a pair of point charges, namely with a positive nucleus and a negative shell, linked by a harmonic bond; whereas in FCM point charges are fixed in certain positions and their values can fluctuate. In particular, influence of polarization effects on equilibrium properties of ionic melts AgI were considered 61 . In Ref.…”
Section: Introductionmentioning
confidence: 99%